Spermine attenuates the preconditioning of diazoxide against transient focal cerebral ischemia in rats. (July 2014) - Zhang, Lin; Wang, Shilei; Dong, Huanli; Li, Yu; Wang, Peng; Li, Shuhong; Guo, Yunliang; Yao, Ruyong
Abstract : It is known that mitochondrial ATP-sensitive potassium channels (mitoKATP ) play a significant role in protecting cerebral function from ischemia–reperfusion injury, which is related with a decrease in the mitochondrial matrix calcium. However, the effect of mitochondrial calcium uniporter (MCU) on diazoxide-induced cerebral protection is still indistinct. The purpose of the present paper is to further observe the relationship between mitoKATP and MCU, and to probe the mechanism. Adult male Wistar rats were randomly divided into five groups: the Sham group, the I–R group, the Dzx+I–R group, the Dzx+Sper+I–R group, and the Sper+I–R group. Rats not in the Sham group were exposed to 2-hour ischemia followed by 24-hour reperfusion. Diazoxide and spermine were administrated 30 minutes before ischemia or 10 minutes before reperfusion, respectively. After 24-hour reperfusion, animals were given neurological performance tests, overdosed with general anesthesia, and then their brains were excised for infarct volume, pathological changes, and apoptosis analysis. The beneficial effects of diazoxide (improved neurological deficits, decreased infarct volume, and apoptosis, evidenced by the decreased expression of cytochrome c and Bax) were significantly neutralized by spermine. The results of the present work suggest that diazoxide-induced cerebral protection against ischemia–reperfusion injury is mediated by spermine through apoptotic pathway.